2023
DOI: 10.3389/feduc.2022.1096889
|View full text |Cite
|
Sign up to set email alerts
|

STEM learning, science identity and immersivity: Giant screen films comparing 2D, 3D, and dome formats including a videogame assessment

Abstract: Multiple assessments, including a novel videogame methodology, were used to understand how viewing a Giant Screen film in four different formats affected both science identity associated with liking science and desire to be a scientist, and learning gains on STEM content. Participants were 406 5th graders who were randomly assigned to watch the 45-min film called Amazon Adventure in either a (1) 2D Small Screen, (2) 2D Giant Flat Screen, (3) 3D Giant Flat Screen, or (4) curved Dome condition. The conditions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Overall, it can be stated that Desktop-VR environments provide a lower level of immersion and, in line with that, a lower level of presence than immersive (headset) VR environments (Smith, 2019). In line with that, Johnson-Glenberg et al (2023) showed in one study that more immersive VR conditions (large 2D-and 3D-screens) outperform a small 2D-screen-condition on learning outcomes. However, not only the degree of immersion and level of presence are influencing factors on the effectiveness of different VR environments, but also the embodiment and the resulting agency might play a role (as shown by another study with a more detailed result pattern by Johnson-Glenberg, 2018).…”
Section: Immersion and Presence In Vr Environmentsmentioning
confidence: 58%
“…Overall, it can be stated that Desktop-VR environments provide a lower level of immersion and, in line with that, a lower level of presence than immersive (headset) VR environments (Smith, 2019). In line with that, Johnson-Glenberg et al (2023) showed in one study that more immersive VR conditions (large 2D-and 3D-screens) outperform a small 2D-screen-condition on learning outcomes. However, not only the degree of immersion and level of presence are influencing factors on the effectiveness of different VR environments, but also the embodiment and the resulting agency might play a role (as shown by another study with a more detailed result pattern by Johnson-Glenberg, 2018).…”
Section: Immersion and Presence In Vr Environmentsmentioning
confidence: 58%
“…Uses of Virtual reality in science learning. (Kurniawati et al, 2020); (Supriadi & Hignasari, 2019); (Ginting et al, 2023) Use of Virtual Reality as a learning medium (Wang et al, 2023); (Elme et al, 2022); (Safadel & White, 2020); (Motejlek & Alpay, 2023) Use of Virtual Reality as a competency test medium (Bao, 2022); (Trudeau et al, 2023); (Larson & Sutton, 1978); (Huang et al, 2022); (Laine et al, 2023); (Wong et al, 2023); (Johnson-Glenberg et al, 2023) Learning & Competency Test in the Film Industry There are several uses for virtual reality in science learning. Use of Virtual Reality as a learning medium: Learning media is anything that can be used to channel messages from the sender to the recipient to stimulate the thoughts, feelings, attention, and interests, as well as the will of students in such a way that the learning process occurs to achieve effective learning goals.…”
Section: Sourcementioning
confidence: 99%